Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.